Revised morphology of Pycnonemosaurus nevesi Kellner & Campos, 2002 (Theropoda: Abelisauridae) and its phylogenetic relationships - Delcourt, Rafael (Zootaxa, 2017)
Abelisaurid theropods were most abundant in the Gondwana during the Cretaceous Period. Pycnonemosaurus nevesi Kellner & Campos, 2002 was the first abelisaurid dinosaur described from the Bauru Group (Brazil, Upper Cretaceous). Nevertheless, its initial description was based on the comparison of a restricted number of remains with other abelisaurids. In this paper, I present a new description of the morphology of Pycnonemosaurus nevesi, including three new caudal transverse processes and a discussion of several new characteristics based on perspectives derived from recently described abelisauroids. Pycnonemosaurus nevesi differs from other abelisaurids based on the following features: a pubis with a small rounded foot and a ventrally-bowed anterior distal end; posterior caudal vertebrae with a hook-shaped transverse process that has an anterodistal expansion that is short and bowed; a strong and massive tibia with a well-developed lateral malleolus that is ventrally expanded. The unfused sutures represent signs of skeletal immaturity, but the specific ontogenetic stage is still uncertain. The current phylogenetic analysis suggests strongly relationship within Pycnonemosaurus and the most-derived abelisaurids (e.g Carnotaurus and Aucasaurus).